2016
DOI: 10.1186/s12864-016-2442-7
|View full text |Cite
|
Sign up to set email alerts
|

Inferential considerations for low-count RNA-seq transcripts: a case study on the dominant prairie grass Andropogon gerardii

Abstract: BackgroundDifferential expression (DE) analysis of RNA-seq data still poses inferential challenges, such as handling of transcripts characterized by low expression levels. In this study, we use a plasmode-based approach to assess the relative performance of alternative inferential strategies on RNA-seq transcripts, with special emphasis on transcripts characterized by a small number of read counts, so-called low-count transcripts, as motivated by an ecological application in prairie grasses. Big bluestem (Andr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…Several gene expression studies indicated that the expression of the majority of lncRNAs is characterized by low abundance 2, 10, 12, 13 , high noise 11 , and tissue-specific expression 10 . These characteristics are very challenging for DE tools, and may potentially negatively affect tool performance 14,15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several gene expression studies indicated that the expression of the majority of lncRNAs is characterized by low abundance 2, 10, 12, 13 , high noise 11 , and tissue-specific expression 10 . These characteristics are very challenging for DE tools, and may potentially negatively affect tool performance 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Following the advent of RNA-sequencing (RNA-seq) technologies, several statistical tools for differential gene expression (DGE) analysis have been introduced. However, low and noisy read counts, such as those coming from lncRNAs, are potentially challenging the tools 14,15 . For example, it is commonly observed that low count genes or transcripts show large variability of the fold-change estimates and thus exhibit inherently noisier inferential behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Following the advent of RNA-sequencing (RNA-seq) technologies, several statistical tools for differential gene expression (DGE) analysis have been introduced. However, low and noisy read counts, such as those coming from lncRNAs, are potentially challenging for the tools [ 10 , 11 ]. For example, it is commonly observed that low count genes show large variability of the fold-change estimates and thus exhibit inherently noisier inferential behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The statistical model used by DESeq2 was chosen to be flexible enough to model a typical RNA-seq experiment. Many benchmarking efforts have demonstrated that DESeq2 generally controls its specificity (the reported p values) and precision (the reported FDR associated with adjusted p values) on real and simulated datasets [31][32][33][34] .…”
Section: Building the Results Tablementioning
confidence: 99%